Pengaruh Masa Kerja, Trait Kepribadian, Kepuasan Kerja, dan Iklim Psikologis Terhadap Komitmen Dosen Pada Universitas Indonesia - Seniati, Liche (UI Scholars Hub, 2006)
The objective of this research are: (1) to verify that tenure and personality trait as personal factors along with job satisfaction and psychological climate as environmental factors affect organizational commitment, and (2) to compare the organizational commitment of lecturers with that of employees in other fields. Respondents of this research are lecturers of Universitas Indonesia who have been working more than one year. Research findings show that tenure, kindness trait, and job satisfaction have direct effects on organizational commitment, while psychological climate has an indirect effect through job satisfaction. These findings strengthen other researches that show how personal and environmental factors affect organizational commitment.